A New Experimental Infection Model in Ferrets Based on Aerosolised Mycobacterium bovis - Lyanne McCallan; David Corbett; Peter L. Andersen; Claus Aagaard; David McMurray; Claire Barry; Suzan Thompson; Samuel Strain; Jim McNair (Veterinary Medicine International)
There is significant interest in developing vaccines to control bovine tuberculosis, especially in wildlife species where this disease continues to persist in reservoir species such as the European Badger (Meles meles). However, gaining access to populations of badgers (protected under UK law) is problematic and not always possible. In this study, a new infection model has been developed in ferrets (Mustela furo), a species which is closely related to the badger. Groups of ferrets were infected using a Madison infection chamber and were examined postmortem for the presence of tuberculous lesions and to provide tissue samples for confirmation of Mycobacterium bovis by culture. An infectious dose was defined, that establishes infection within the lungs and associated lymph nodes with subsequent spread to the mesentery lymph nodes. This model, which emphasises respiratory tract infection, will be used to evaluate vaccines for the control of bovine tuberculosis in wildlife species.